The Human Cost of Political Conflict: Trauma, Ethics, and Memory in Mirza Waheed’s “The Collaborator" (IUBAT Review, 2026)
This paper explores the psychological and ethical dimensions of political violence in Mirza Waheed’s “The Collaborator”, focusing on the human cost of the Kashmir conflict during the late 1980s and early 1990s. The study examines how trauma, memory, and moral ambiguity are represented through the unnamed protagonist—a young Kashmiri coerced into working for the Indian military to recover identification from fallen insurgents. Grounded in Cathy Caruth’s theory of trauma and Judith Herman’s PTSD framework, this paper analyzes how the novel articulates the internal collapse of individuals caught in systemic violence. Using close textual analysis, the study reveals how personal suffering intersects with broader political agendas, leading to alienation, cultural erosion, and existential crisis. The protagonist’s experiences of grief, fear, and identity loss illustrate the devastating psychological consequences of living in a militarized zone. The findings highlight how literature can convey the inner world of trauma victims and bring attention to the lived realities of conflict-affected populations. By shifting the analytical focus from geopolitical narratives to human experiences, the paper contributes to literary trauma studies and underscores the necessity of empathetic engagement with war literature.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 01-21